(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
This research aims to forward the role of challenges in marketing the service (expatriate labor, male and female, and perfecting the body language) in attracting or alienating customers because they have a great role in religious tourism and was chosen from the religious tourism sites of Najaf and Kufa for the post 2003 period. (48) questionnaire. The research hypotheses were tested using a set of statistical methods and by relying on the SPSS program using the questionnaire as a main tool for collecting the necessary data and information from the research sample. The research reached a number of conclusions. Services (expatriate workers, male and female, and mastery of the body) language has a key role in attracting or alienating customers in the religious tourism sites.The research concluded with a number of recommendations: the need to address these challenges in one package or separately, which leads to attracting customers to religious tourism sites widely.